Validação de modelo de elementos finitos para análise de juntas coladas como alternativa às análises experimentais - Thaiane Oliveira Toscano Ximenes (2022)
Bonded joints are increasingly used as an alternative to traditional fastening methods. However, one of its main disadvantages is the experimental analysis due to cost and required time. This work aims to validate a methodology to perform finite element analysis of bonded joints. For this purpose, this work was carried out in two stages. The first one to validate the method used the existing theoretical models as a reference and obtained the results with a slight variation of 0.34%, demonstrating that the script worked properly. Additionally, considering that damages in bonded joints are very likely during its manufacturing, the script was tested for a damaged bonded joint to obtain an increase in the maximum Von Mises stress in the region of the failure. As a result, an increase of 38% was obtained, demonstrating again the effectiveness of the model. In the second stage, the script was applied to the model of an actual bonded joint, where a comparative study was carried out concerning the results obtained experimentally. Two models were used, one with an aluminum substrate and one with a carbon fiber substrate, both aged or not through exposure to UV light and with or without graphene. The results demonstrated compatibility with the experimental results, based on two analyses. The first one proved that the samples that used carbon fiber could withstand a load of approximately 9% more than the samples that used aluminum substrate, results that are compatible with the ones obtained experimentally. The second analysis studied the behavior of samples that used graphene and were aged through exposure to UV light, compared to standard samples, without graphene and aging. As a conclusion, the stress distributions of the joints obtained through the analysis of finite elements were analyzed, where it was possible to observe that the critical region of the failure is compatible with the analytical solution, i.e., it is in the region of singularity.